COLLABORATIVE GOVERNANCE MITIGASI BENCANA BANJIR DI INDONESIA: SYSTEMATIC LITERATURE REVIEW (SLR) DARI TAHUN 2018-2023 - Alvina Hapsari, Amanda Alvina Hapsari; Zarkasyi Rahman, Amni (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2025)
Much research has been carried out regarding collaborative governance in flood disaster mitigation. However, there has been no research regarding the structure of knowledge development on the topic of collaborative governance, flood disaster mitigation. Therefore, it is necessary to understand collaborative governance for flood disaster mitigation through a systematic literature review process as an effort to find novelty. The systematic literature review process was carried out using PRISMA guidelines. The literature search site used is Google Scholar. The inclusion criteria for the selected articles are: 1) Published in English and Indonesian, 2) Published from 2018-2023, 3) Availability of literature using articles with full text, 4) Publication stage in the form of final press and 5) Document type in the form of a journal . The development of publications in the field of collaborative governance in flood disaster management in Indonesia shows an increase in numbers from year to year, with the most publications in the period 2018 to 2023, namely in 2023 with the prominent keyword